Representações no jornalismo popular: a cidadania no discurso do Extra (RJ) - Prevedello, Carine Felkl (2008)
The end of 1990 s is marked by successive appearing of new models of popular newspapers in Brazil. Directed to C social class, which widespread their potential of consume in accordance with economical changes occurred in the same period, the popular newspapers have been searching for shortening the bond with the reader throughout a journalism centered in the realization of services, entertainment and themes related to people s daily life. As the journalism occupies a central place in the contemporary public sphere, what defines it as a legitimate instance that offers a discourse of credibility; the journalism is simultaneously a space which shelters social representations. The journalism discourse, which is constructed by an inevitable social repercussion power and tensioned by opposite views, produces representations based on ideological pre-constructions that define determined subject positions. In this way, by working with the information that is interesting to its public and as a communicative vehicle offered to the population and characterized as a directed-truth discourse, the journalism discourse has a compromise with the citizenship construction. The civil, political and social rights that constitute the citizenship dimension are the journalistic discourse object, and are represented by different ways according to the image that the newspaper and the journalists attribute to their readers. Extra newspaper, established by Infoglobo in Rio de Janeiro in 1998, is consolidated as the most popular newspaper in Brazil and reached in 2006 the first place in circulation among Brazilian readers. Since 2006, it is alternating the first positions with the reference newspapers that are recognized historically as information source and linked to the opinion former social class. In this perspective, the study of the discourse functioning in a popular newspaper which begins to dispute with the most important newspapers in Brazil becomes important to identify the meanings that are circulating and producing representations through popular journalism. This present work analyzed discourse sequences published in Extra in two weeks that were related to Education, Public Health, Work, Security, Customer s Rights and Politics as basic categories to define the concept of citizenship and to identify the recurrent meanings in Extra s discourse. Through methodological aspects of Discourse Analysis and by using the paraphrase to define the meanings from the reiterations we identified paraphrase families that delimitated the representation constructed by Extra concerning the rights about the newspaper and about the reader in the perspective of citizenship. The Discourse Formations named in the research as Attributed and Fragile Citizenship one that are predominant in Extra s discourse, and Assumed and Active Formations, minor ones, allowed to comprehend that the newspaper gives importance to the reproduction of a low marginalized class context in terms of access to the rights by maintaining, paralelly a sort of slit to the citizenship action through the protests and the search of orientation to exercise citizenship.